Case Report: Massive Hematocel with An Intrauterine Pregnancy - Qonita Prasta Agustia; Halida Nelasari; Sutrisno (Ikatan Dokter Indonesia Wilayah Jawa Timur, 2022)
Introduction: Incidence of ectopic pregnancy can be an acute or chronic condition. The condition of chronic ectopic pregnancy itself is unique, arises from a minor rupture, and then develops into a hematocele. Chronic ectopic pregnancy is quite complicated to diagnose because it usually has a prolonged clinical course and can disappear spontaneously. Case Presentation: A woman aged 31-32 weeks, aged 24 years, complained of right abdominal pain accompanied by nausea and vomiting. Examination of vital signs was 120/80 mmHg, pulse 84 x/min, RR 20x/min, temperature 36.70C, and SpO2 of 98% with pale conjunctiva and abdominal tenderness in the right upper quadrant. On laboratory examination, the patient found severe microcytic normochromic anemia (Hb 4.5 mg/dl; MCV 96.6 Fl; MCH 30.2 pg), thrombocytopenia (platelets 133,000 L) and hypoalbumin (albumin 2.82 L). Ultrasound examination showed a mass in the right adnexa accompanied by intrauterine pregnancy. The patient underwent a laparotomy and found a mass in the form of a blood clot (hematocele) of 30x20x20 cm. Conclusion: Chronic ectopic pregnancy is a rare condition, especially in developed countries. A clinician should be more detailed in diagnosing and considering the ultrasound, an amorphous mass with avascularity to amass with complex vascular formation. This is very necessary considering that this hematocele mass can develop progressively to cause fetal growth disorders.